Evaluation of Nutritional Status of Children below 5 Years of Age for Valuation of Rickets Caused by Nutritional Deficiency - Gul E Lala, Nighat Jabeen, Saba Afzal Shaikh, Qamar Uz Zaman Shahzad, Hassan Ul Haq, Abid Rafique Chaudhry (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the nutritional status of children under five-years of age, the factors related to it and the degree of malnutrition. Study Design: A cross-sectional study. Place and Duration: In the department of Paediatrics, Hayatabad Medical Complex, Peshawar for the duration of six months from July, 2021 to Dec, 2021. Methods: Using a non-probability-based convenient sampling technique, approximately 130 children under the age of five were selected. The nutritional status and physical development of children was assessed with simple anthropometric technique. A partially pre-tested organised survey form was given to collect the data by face-to-face interviews with the mothers of the children. SPSS version 22.0 was applied for data collection and to estimate percentages and numbers. Results: Of 130 children, 80(61.5%) were male and 50(38.5%) were female. According to the classification of Gómez's, 102 children had Malnutrition out of 130 children; 55 (42.3%) had grade I, and 24 (18.5%) had grade II and 23 (17.7%) had grade III malnutrition. Of 80 children, 32.3% had mild stunned growth, 16.9% moderate stunned growth, and 12.3% severe stunned growth. When status of immunization was calculated, 32 (24.6%) were nonimmunized, partially immunization was seen in 65 (50%) children and fully immunization in 33 (25.4%) cases. Of the 98 uneducated mothers, 60(63.2%) had malnourished children, 70(71.4%) had Kwashiorkor, and 28(28.6) had marasmus. Of 130 children, 90 were breastfed and children on bottle-fed were 40. Conclusions: The malnutrition rate was augmented among children <5 years of age (78.6%) due to inadequate eating habits. Accompanying influences were insufficient immunization and illiterate mothers. The education regarding health counting adequate weaning, exclusive breastfeeding, family planning and routine immunization via schedule of EPI should be encouraged. Keywords: Nutritional status, Child, Risk factors, Protein and Energy malnutrition.